Controlling angular dispersions in optical metasurfaces - Zhang, Xiyue (Light Sci Appl, 2020)
Although metasurfaces have shown great potential for manipulating light, most previously realized meta-devices suffer from uncontrolled angular dispersions, making them unfavorable for many applications. Here, we propose a general strategy to realize optical metasurfaces with desired angular dispersions based on carefully controlling both the near-field couplings between meta-atoms and the radiation pattern of a single meta-atom. Utilizing such a strategy, we experimentally demonstrate a series of optical meta-devices with predesigned angular dispersions, including two incident-angle-insensitive absorbers, one incident-angle-selective absorber, and one multifunctional meta-polarizer whose functionality changes from a perfect mirror to a half-waveplate as the excitation angle varies. Finally, we design a gradient meta-device using meta-atom arrays with purposely controlled angular dispersions and numerically demonstrate that it can exhibit distinct wavefront-control functionalities when illuminated at different incident angles. Our findings establish a new platform for achieving angle-multiplexed functional meta-devices, significantly expanding the wave-manipulation capabilities of optical metasurfaces.